What drives quality improvement in chronic kidney disease (CKD) in primary care: process evaluation of the Quality Improvement in Chronic Kidney Disease (QICKD) trial - Simon de Lusignan; Nicola Thomas; Hugh Gallagher; Mohammad Aumran Tahir; Akin Nihat (BMJ Open, 2016)
Objectives This study is a process evaluation of the Quality Improvement in Chronic Kidney Disease (QICKD) study, comparing audit-based education (ABE) and sending clinical guidelines and prompts (G&P) with usual practice, in improving systolic blood pressure control in primary care. This evaluation aimed to explore how far clinical staff in participating practices were aware of the intervention, and why change in practice might have taken place.Setting 4 primary care practices in England: 2 received ABE, and 2 G&P. We purposively selected 1 northern/southern/city and rural practice from each study arm (from a larger pool of 132 practices as part of the QICKD trial).Participants The 4 study practices were purposively sampled, and focus groups conducted with staff from each. All staff members were invited to attend.Interventions Focus groups in each of 4 practices, at the mid-study point and at the end. 4 additional trial practices not originally selected for in-depth process evaluation took part in end of trial focus groups, to a total of 12 focus groups. These were recorded, transcribed and analysed using the framework approach.Results 5 themes emerged: (1) involvement in the study made participants more positive about the CKD register; (2) clinicians did not always explain to patients that they had CKD; (3) while practitioners improved their monitoring of CKD, many were sceptical that it improved care and were more motivated by pay-for-performance measures; (4) the impact of study interventions on practice was generally positive, particularly the interaction with specialists, included in ABE; (5) the study stimulated ideas for future clinical practice.Conclusions Improving quality in CKD is complex. Lack of awareness of clinical guidelines and scepticism about their validity are barriers to change. While pay-for-performance incentives are the main driver for change, quality improvement interventions can have a complementary influence.